Democratic participation in Colombia and vote for public education (2014)
Despite having the tools to exercise an awareness and active participation democratically, reality evidence that democratic participation is largely permeated by personal interests, some degree of ignorance, lack of empowerment, lack of commitment and social manipulation. The goals of the democratic tools has become blurred and the message is clear, democracy in the country is not showing what citizens and the general public need and they are not interested enough in the what to do democratic. If we start with our children in schools by strengthening their education in this participatory culture at all levels to act as citizens, so it is essential to change our political culture, benefit from these mechanisms and exercise on their own and not on behalf of the interests of others or worst, by neglect in the name of ignorance or laziness participatory because culturally it has been shown that most Colombians do not participate simply because they delegate to others this democratic exercise. Therefore it is intended to situate the simply reading of the various mechanisms of citizen participation and evidence that it are not that far to accomidate them or at least one in particular and exercise our right without fear instead increasingly demanding more from our leaders, because somehow the more we participate more sue the performance of their duties and commitments.